Africa and the US national security policy in a changing global order (2009)
Developments in US policy towards Africa since 9/11, as shown by the establishment of the Africa Command, has been described as marked departures from what existed in the immediate post-Cold War era when Africa was 'neglected'. Africa has been de-marginalized in the US strategic and national security policy because it has become critical to the strategic interest of the US. This paper provides an alternative interpretation of the US national security policy as translated into activities in Africa in the post 9111period. It argues that Africa has never been marginalized nor neglected by the US in its foreign or security policy after the Cold War, although there has been a change in strategy. This becomes obvious when security is not separated from the economy in the analysis of the US national security policy agency towards Africa